PENURUNAN BILANGAN PEROKSIDA PADA MINYAK JELANTAH MENGGUNAKAN SERBUK DAUN PEPAYA - Fandhi Adi Wardoyo (Universitas Muhammadiyah Semarang, 2018)
Research on the reduction of peroxide numbers in wasted cooking oil has been done. The aim of this research is to determine the reduction of peroxide numbers in wasted cooking oil after soaking with papaya leaf powder (Carica papaya) concentration 5, 10, 15 and 20 %b/v, then it has been soaked for one to five days. The wasted cooking oil has initial peroxide numbers sebesar 74,29 mg O2/100. The result showed that after wasted cooking oil has been soaked for five days with papaya leaf powder concentration 10%b/v can reduced peroxide number up to 52,16%, and the peroxide number decreased to 35,54 mg O2/100.